Linguistic Politeness in Rural Areas: The Spiš Dialect in Poland - Grochola-Szczepanek, Helena (Jezikoslovni zapiski, 2015)
This article presents a model of linguistic politeness in the Polish Spiš dialect. The author discusses forms of address, greetings, and farewells, and also draws attention to deviations from the accepted conventions and new polite forms in rural areas.